Perlindungan Hukum Terhadap Pekerja atas Upah yang Terlambat Dibayarkan: Tinjauan Hukum atas Penerapan Teori Keadilan: Legal Protection for Workers for Late Payment of Wages: Legal Review of the Application of the Theory of Justice - Andi Sri Rezky Wulandari; Mira Nila Kusuma Dewi; Andi Rahmah (Faculty of Law, Universitas Brawijaya, 2022)
Wages have always been an issue that creates confusion between workers and employers as employers, which will continue to be a long-lasting problem if not handled properly. It is hoped that legal arrangements will be formed that will at least reduce the unequal interests between the two which gradually give rise to disharmony. Throughout labor history, the payment of workers' wages, which is a worker's right, has always given rise to problems, even though wages are the basis for meeting the needs of life and family. The purpose of this writing is to analyze and examine legal protection for workers for late payment of wages based on John Rawls's Theory of Justice. The research used is normative legal research with a statutory regulation approach and a case approach. The legal materials used are primary, secondary and tertiary legal materials. The results of this research show that work agreements protect workers against late payment of wages. The legal implications of workers' wages being paid late are (1) giving rise to industrial relations disputes; (2) The principle of justice is not realized in employment relations; (3) Injuring workers' welfare. Meanwhile, preventive efforts that must be taken to prevent workers' wages from being paid late are through optimizing the guidance and supervision of the implementation of harmonious employment relations with statutory regulations.